ANALISIS BERPIKIR KRITIS BERBASIS ETNOMATEMATIKA PADA KONSEP GEOMETRI DALAM PERMAINAN GOBAK SODOR - Tino Gagah Aprillian; Eric Dwi Putra; Aswar Anas (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
The aim of this research is to describe students' critical thinking in solving ethnomathematics-based mathematics problems on geometric concepts. This type of research is descriptive qualitative research. The research subjects were class VII students at As–Syuja'i Middle School. Critical thinking is an important ability that must be developed in students in learning mathematics. Critical thinking skills can be developed through learning mathematics using an ethnomathematics approach with the traditional game Gobak Sodor which has the potential to be used as an interesting learning medium in introducing geometric concepts to students. The results obtained by using an ethnomathematics approach with the traditional game gobak sodor, namely students' critical thinking in solving mathematical problems based on high ability and low ability types. Students who have high ability carry out all stages of solving mathematical problems using critical thinking indicators accurately and correctly, whereas students who have low ability do not carry out the stages of solving mathematical problems using critical thinking indicators accurately and correctly, only that students can determine what is being asked. on the questions correctly at the stage of understanding the problem with critical thinking indicators.